Rapid extraction of fertilizer from palm oil mill effluent (POME) using Magnesium Ammonium Phosphate (MAP) precipitation method and Fe-Chloro Polyacetamide (FeCP) electrolyte system - Nur Ain Farhana, Ghani (2017)
Palm oil mill effluent (POME), a residual liquid waste obtained after extraction of oil from the fruits of oil palm is considered one of the main source of contamination of watercourse in Malaysia. POME contained significant amount of nutrients, organic matter and total suspended solids. Recovery of nutrients from POME would be beneficial for agricultural purposes. Various available system exist in treatment ofPOME however, these systems failed to utilize the nutrient contained within POME as the nutrients were completely removed during treatment. The use of Magnesium Ammonium Phosphate (MAP) precipitation method have been shown to provide effective approach in treating wastewater containing substantial amount of nutrients, at the same time produce high quality fertilizer. Previous studies have showed that MAP precipitate or struvite recovered from wastewater is a viable method for pre-treatment of wastewater. Similarly, the use of biological based coagulation method such as Fe-Chloro Polyacetamide (FeCP) electrolyte system is used for its capability of destabilizing and aggregating colloids in wastewater. The by-product of both techniques contained high amount of nutrients that may be used as fertilizers. In this study, both MAP and FeCP is proposed and evaluated to recover nutrients essential for plant growth from raw POME. A lab-scale study was performed to investigate the efficiency of struvite precipitation method in extracting struvite minerals. Struvite precipitation was carried out on raw POME using MgCI2.6H20 + Na2HP04.l2H20 at pH 8, 9 and 10. Additionally, FeCP method was tested with and without the addition of FeCI3 to identify the treatment efficiency. The treatment was analyzed based on the effect of chitosan dosage, pH and mixing of time. At the end of the test, the characteristics of precipitates and improvement in the water quality parameters were evaluated. In addition, the fertility of the precipitate was evaluated by a set of pot trial tests using Scindapsus Aureus. Test results indicated that, the BOD/COD ratio of the POME was found to be very high (i.e. 2.58), indicating that high amount of organic are readily degradable. After MAP precipitation tests, 85.56% ammonium nitrogen was recovered. The precipitate extracted in this study was found to have excess water content. Purification process improved the quality of the precipitate obtained. X-ray diffraction (XRD) analyses indicated that, after purification, the MAP precipitate is similar to that of pure struvite. Energy Dispersive XRay Spectrometry (EDX) analysis of MAP precipitate confirmed that the precipitate had similar Mg/N/0/P ratio to that of pure struvite. Surprisingly, X-ray Fluorescents (XRF) revealed that some traces of heavy metals existed in all precipitates obtained using different techniques. Based on the fertility tests, it was found out that the growth of Scindapsus Aureus using chitosan without FeCh and MAP precipitates obtained in this study were far superior as compared to the growth of Scindapsus Aureus using commercially available fertilizer. Improvements in the water quality parameters were achieved, and were found to be lower than the allowable regulatory discharge limits.